Ramethy: Reconfigurable acceleration of bisulfite sequence alignment - Arram,J; Luk,W; Jiang,P (2015)
This paper proposes a novel reconfigurable architecture for accelerating DNA sequence alignment. This architecture is applied to bisulfite sequence alignment, a stage in recently developed bioinformatics pipelines for cancer and non-invasive prenatal diagnosis. Alignment is currently the bottleneck in such pipelines, accounting for over 50% of the total analysis time. Our design, Ramethy (Reconfigurable Acceleration of METHYlation data analysis), performs alignment of short reads with up to two mismatches. Ramethy is based on the FM-index, which we optimise to reduce the number of search steps and improve approximate matching performance. We implement Ramethy on a 1U Maxeler MPC-X1000 dataow node consisting of 8 Altera Stratix-V FPGAs. Measured results show a 14.9 times speedup compared to soap2 running with 16 threads on dual Intel Xeon E5-2650 CPUs, and 3.8 times speedup compared to soap3-dp running on an NVIDIA GTX 580 GPU. Upper-bound performance estimates for the MPC-X1000 indicate a maximum speedup of 88.4 times and 22.6 times compared to soap2 and soap3-dp respectively. In addition to runtime, Ramethy consumes over an order of magnitude lower energy while having accuracy identical to soap2 and soap3-dp, making it a strong candidate for integration into bioinformatics pipelines.